Silent Sabotage: The Role of Dark Triad Leadership in Employee Turnover and HR Dysfunction (Journal of Asian Development Studies, 2025)
Dark triad leadership is an invisible, internal danger that affects employees' health and employee turnover and deteriorates HR systems. These leaders, known as narcissistic, machiavellian, and psychopathic, erect an atmosphere of fear, manipulation, emotional fatigue, and moral decay. Leadership is one of the most important factors affecting an organization's success, employee satisfaction, and workplace stability. But not all leadership is beneficial. Dark triad leadership has become a growing area of academic research, but several important gaps remain. First, most studies examining the dark triad traits have done so separately and have not investigated the overall organizational effect of the dark triad. Second, HR dysfunction is an enabling mechanism that receives insufficient attention in the literature, which focuses more on employee psychological distress. A recent systematic review concluded that more research is needed on the moderators and mediators of organizational outcomes in dark triad leadership. The present study uses a quantitative explanatory research design. The objective measurement of relationships among variables is based on positivist philosophy. The research methodology adopted in the study is a deductive approach grounded in theories of organizational behavior. The targeted audience is: employees, HR professionals, mid-level staff, and private and public sector workers. There will be about 300 respondents. Stratified random sampling will be used. Structured questionnaires will be used with a five-point Likert scale to collect primary data. Academic journals, organizational reports, leadership studies, HR literature, and data analysis will be used as secondary data.